Implementasi Keterbukaan Informasi Publik pada Humas Kota Bekasi di Era Digital - Aat Ruchiat Nugraha (Jurnal Ilmu Komunikasi PROGRESSIO, 2022)
In managing data, there are still many institutions that do it manually and are ineffective and efficient. In response to this, the Public Relations Section of the Bekasi City Regional Secretariat created a technology-based application system for the management of e-clippings and data releases belonging to the Public Relations Department, namely Saker Humas. This article aims to find out the function of the Saker Pr public relations website as a medium for public information disclosure. The research method used is a qualitative descriptive method with data collection techniques in the form of interviews, observations, and literature studies. The results showed that the Saker Humas website has the function of making it easier for employees of the Public Relations Department to find information needed by external parties. The management of the Saker Humas website serves to foster a responsive and informative attitude of the Bekasi City government as part of the functions and duties of the Main PPID carried out by the Public Relations Department regarding public information disclosure.